Antioxidant Activity From Multiple Extraction Of Kratom Leaf (Mitragyna speciosa) Without Veins With Sonicator-Type Bath - Sulvi Purwayantie; Dzul Fadly; Sholahuddin; Nur Endah Saputri; Sri Wijanarti (Media Publikasi Cendekia Indonesia, 2022)
Kratom is one of the export commodities from West Kalimantan, containing alkaloids that are beneficial to health. The export product currently in demand is extracted flour. So far, the most widely used extraction method is conventional single extraction, using maceration which is inefficient, long and consumes a lot of solvents. This study examined the process of alkaloid extraction using the technology of drying with a microwave and extraction using a sonicator. The study aimed to determine the microwave drying method which produces kratom leaf alkaloid levels and the type of solvent which produces the strongest IC-50 antioxidant properties from the bath-type sonicator multilevel extraction method. The research method was divided into 2 stages, namely, stage 1 drying with 2 ingredients, kratom leaves with veins and without veins, then tested for alkaloid levels. The leaves material with high alkaloids was continued for phase II of the IC-50 antioxidant property test from various solvents (hexane, methanol, ethanol) using multilevel extraction with a bath-type sonicator. Data analysis was carried out descriptively. The results showed that leaves without veins produced relatively higher levels of alkaloids than leaves with veins. The type of burner that produced IC-50 antioxidant activity was 0.3 ppm ethanol extract. Thus, these results can be a recommendation to stakeholders